ANALISIS KINERJA KEUANGAN PT KIMIA FARMA Tbk SEBELUM DAN SELAMA PANDEMI COVID-19 - Setia, Rini (Universitas YPPI Rembang, 2022)
The purpose of this study is to determine whether there is an influence of the Covid-19 pandemic on the financial performance of the company PT Kimia Farma Tbk. This research uses a quantitative descriptive approach with secondary data sources obtained from the Indonesia Stock Exchange or the official website of PT Kimia Farma. Financial statement data for 2018-2019 is used as a reflection of before the Covid-19 pandemic conditions, while financial statement data for 2020-2021 is used as a reflection of conditions during the Covid-19 pandemic. The performance analysis that will be used is the liquidity ratio analysis of the Current Ratio (CR) model, the leverage ratio analysis of the Debt to Equity Ratio (DER) model, the profitability ratio analysis of the Return On Asset Ratio (ROA) model, and the activity ratio analysis of the Receivable TurnOver model (RTR). The results of this study show that there is an influence of the Covid-19 pandemic on financial performance at PT Kimia Farma Tbk. So that before the pandemic the company experienced a decline in financial performance, while during the Covid-19 pandemic there was an increase in financial performance.Keywords: Financial Statements, Financial Ratios, Financial Performance